Współdziałanie gminy z podmiotami prywatnymi w zakresie działalności sportowej na gruncie Ustawy o gospodarce komunalnej i Ustawy o sporcie - Soroka, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This paper focuses on the problem of cooperation between the local government on the lowest level and sport clubs. It explains how the local government can invest in or finance sport clubs on the ground of the Act on municipal services and the Act on sport. Both of these acts contain regulations which allow local governments to either aid or to perform actions in the field of sport. A very important question is whether such activities can be perceived as public utility activities.
Keywords: ustawa o sporcie; ustawa o gospodarce komunalnej; gmina; podmioty prywatne; współdziałanie; działalność sportowa